High vacuum-assisted extraction affects virgin olive oil quality: Impact on phenolic and volatile compounds. (16th April 2021) - Taticchi, Agnese; Esposto, Sonia; Veneziani, Gianluca; Minnocci, Antonio; Urbani, Stefania; Selvaggini, Roberto; Sordini, Beatrice; Daidone, Luigi; Sebastiani, Luca; Servili, Maurizio
Graphical abstract: Highlights: Introduction of high vacuum technique in VOO extraction system. High vacuum treatment increases the size of oil drops in the malaxed olive pastes. Increases in the phenolic contents in VOO and changes in the volatile fractions. Reduction in VOO volatile compounds related to flavor and off-flavor. Abstract: High vacuum technology has been incorporated into a new assisted extraction system applied to virgin olive oil (VOO) processing, which was tested at a lab-scale pilot plant to evaluate its impact on the physicochemical properties of the olive paste and oil. The vacuum system induced changes in the mechanical and structural properties of the olive cells, improving the coalescence of the oil droplets due to substantial cellular and intracellular mass transfer during the process, as shown by cryo-scanning electron microscopy (Cryo-SEM) analysis. The effects on the quality characteristics of VOOs extracted from three cultivars at different malaxation temperatures were evaluated. A significant increase in the phenolic content, from 25.2% to 48.6%, was observed. The content of volatile compounds responsible for the VOO flavor decreased as a function of malaxation temperature. The reduction of some volatile molecules related to the VOO off-flavor (ethanol, ethyl acetate and acetic acid) was also shown.